2020
DOI: 10.1111/jbi.13753
|View full text |Cite
|
Sign up to set email alerts
|

Climate and food resources shape species richness and trophic interactions of cavity‐nesting Hymenoptera

Abstract: Aim Temperature, food resources and top‐down regulation by antagonists are considered as major drivers of insect diversity, but their relative importance is poorly understood. Here, we used cavity‐nesting communities of bees, wasps and their antagonists to reveal the role of temperature, food resources, parasitism rate and land use as drivers of species richness at different trophic levels along a broad elevational gradient. Location Mt. Kilimanjaro, Tanzania. Taxon Cavity‐nesting Hymenoptera (Hymenoptera: Api… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
55
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(63 citation statements)
references
References 65 publications
6
55
2
Order By: Relevance
“…Temperature, which has been shown to be one of the most important factors for driving species diversity patterns of multiple taxa at Mt. Kilimanjaro (Peters et al 2016), but also for cavity-nesting Hymenoptera (Mayr et al 2020), was positively correlated with the nest-building activity of spider-hunting wasps, while relative humidity decreased it. Spider abundances at Mt.…”
Section: Synchronised Nesting-activity Between Bees and Wasps In The mentioning
confidence: 97%
See 2 more Smart Citations
“…Temperature, which has been shown to be one of the most important factors for driving species diversity patterns of multiple taxa at Mt. Kilimanjaro (Peters et al 2016), but also for cavity-nesting Hymenoptera (Mayr et al 2020), was positively correlated with the nest-building activity of spider-hunting wasps, while relative humidity decreased it. Spider abundances at Mt.…”
Section: Synchronised Nesting-activity Between Bees and Wasps In The mentioning
confidence: 97%
“…(Supplementary material, Fig. S1), which we identified as the upper limit of the distribution of cavity-nesting Hymenoptera in a previous study (Mayr et al 2020). Study sites covered five major ecosystem types found at the southern slopes of Mt.…”
Section: Study Region and Study Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Niche breadth surely impacts ecological macro-pattern, and insects will allow testing concepts and predictions over a large range of specializations. Several recent studies used the unique feeding habits of insects to investigate the more-individuals hypothesis and its inherent links among productivity, food availability, abundance, and richness along elevational gradients (Classen et al, 2015, Gebert et al, 2020, Mayr et al, 2020.…”
Section: Make Use Of Ecological Specialization and Trait Variabilitymentioning
confidence: 99%
“…A. Johnson, 2013;Pichler, Boreux, Klein, Schleuning, & Hartig, 2020). The second problem is that the role of individual floral traits and the related selection pressures can vary in space and time (Abrahamczyk, Kluge, Gareca, Reichle, & Kessler, 2011;Albrecht et al, 2018;González et al, 2009;Hawkins & Devries, 2009;Mayr et al, 2020;J. Mertens et al, 2020;Fig.…”
Section: Introductionmentioning
confidence: 99%